Research on the impact of clan network on farmers’ entrepreneurial income—The case of China - Jiang, Xiaoli; Wu, Qianwen; Wang, Lina; Jiang, Beirui; Ma, Xiao (Frontiers in Psychology, 2022)
Farmers' entrepreneurial income is related to poverty alleviation and common prosperity. The clan network is an important social capital for farmers. However, research on effects of this relationship is still scant. We classifies farmers' social capital as endowed social capital such as clan networks and leapfrogging social capital that needs to be operated. Using the data of CFPS 2010-2018 in China, this study investigates the influence of clan networks and farmers' entrepreneurial income. Based on the social capital theory,we adopt a semilogarithmic model, and propensity score matching method for robustness checks. The results show that the clan network, as an endowed social capital of farmer, has a significant and positive effect on entrepreneurial income for both men and women. And The clan network has the greatest impact on middle-income farmers. Our results have important implications for policymakers in other developing economies who seek to increase farmers' income.